Proceedings of the 2016 ACM International Joint Conference on Pervasive and Ubiquitous Computing 2016
DOI: 10.1145/2971648.2971740
|View full text |Cite
|
Sign up to set email alerts
|

CrossCheck

Abstract: Early detection of mental health changes in individuals with serious mental illness is critical for effective intervention. CrossCheck is the first step towards the passive monitoring of mental health indicators in patients with schizophrenia and paves the way towards relapse prediction and early intervention. In this paper, we present initial results from an ongoing randomized control trial, where passive smartphone sensor data is collected from 21 outpatients with schizophrenia recently discharged from hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 214 publications
(89 citation statements)
references
References 49 publications
0
89
0
Order By: Relevance
“…But as Spencer’s case shows, sometimes a smartphone app is not the solution. There is also growing excitement about the potential of big data in mental health and using smartphones and sensors to gather tremendous amounts of data from those with mental illness, in order to uncover new insights [7]. Passive data, sensor data gathered without active user engagement (e.g., step count collected automatically by a fitness tracker versus active button presses on a tally counter), is an accelerating area of health research now.…”
Section: Brief Discussionmentioning
confidence: 99%
“…But as Spencer’s case shows, sometimes a smartphone app is not the solution. There is also growing excitement about the potential of big data in mental health and using smartphones and sensors to gather tremendous amounts of data from those with mental illness, in order to uncover new insights [7]. Passive data, sensor data gathered without active user engagement (e.g., step count collected automatically by a fitness tracker versus active button presses on a tally counter), is an accelerating area of health research now.…”
Section: Brief Discussionmentioning
confidence: 99%
“…Clinicians need to track schizophrenia patients' symptom states to identify risks and adjust treatment as necessary. At the CrossCheck study [1,2,3] partner hospital, Zucker Hillside Hospital, in New York City, schizophrenia outpatients regularly schedule clinical visits with their clinicians. The time between visits varies from once a week to once a month, depending on the patients' symptom severity and risk.…”
Section: [Highlights]mentioning
confidence: 99%
“…Th e CrossCheck study is an ongoing randomized controlled trial [6] conducted in collaboration with a large psychiatric hospital, Zucker Hillside Hospital, in New York City [3]. Th e study aims to recruit 150 participants for 12 months using rolling enrollment.…”
Section: Crosscheck Studymentioning
confidence: 99%
“…The StudentLife project used mobile sensing technology to monitor the daily behavior of college students and found that the tracked behaviors were associated with students’ mental states, such as stress [12]. The CrossCheck project used data collected from phone sensors and ecological momentary assessment to build models to predict mental health indicators in schizophrenic patients based on phone sensor data [8]. In addition, mobile technologies have been shown to have advantages in delivering mental health therapies [13,14].…”
Section: Introductionmentioning
confidence: 99%